The Effect Of Internal Locus Of Control And Fraud Seriousness Level On Whistleblowing Intention: The Mediating Role Of Organizational Commitment - Annisa Dwi Kurnia; Lismawati Lismawati; Nurna Aziza (UNIVED Press, 2026)
This study aimed to explore the effects of internal locus of control and fraud seriousness levels on whistleblowing intention, with organizational commitment as a mediating variable. SEM-PLS method was employed with the support of SmartPLS 4 software to analyze the data. Based on the findings, internal locus was found to have a positive effect on organizational commitment. Additionally, organizational commitment was also found to positively affect whistleblowing intention. Despite the findings, internal locus of control and fraud seriousness level had no direct association with whistleblowing intention. The result of mediation analysis indicated that organizational commitment functioned as a mediator between internal locus of control and whistleblowing intention. This suggested that the effect of internal locus of control on whistleblowing intention occurred through organizational commitment as a mediating variable (full mediation). In comparison, no mediating effect of organizational commitment was found in the relationship between fraud seriousness level and whistleblowing intention. The implications of this study emphasized the importance of strengthening organizational commitment and developing employees’ internal characteristics to enhance their willingness to report misconduct. Furthermore, the findings theoretically supported the Theory of Planned Behavior.